SoxE group transcription factor Sox8 promotes astrocytic differentiation of neural stem/precursor cells downstream of Nfia - Jun Takouda; Sayako Katada; Takuya Imamura; Tsukasa Sanosaka; Kinichi Nakashima (Wiley, 2021)
Abstract The brain consists of three major cell types: neurons and two glial cell types (astrocytes and oligodendrocytes). Although they are generated from common multipotent neural stem/precursor cells (NS/PCs), embryonic NS/PCs cannot generate all of the cell types at the beginning of brain development. NS/PCs first undergo extensive self‐renewal to expand their pools, and then acquire the potential to produce neurons, followed by glial cells. Astrocytes are the most frequently found cell type in the central nervous system (CNS), and play important roles in brain development and functions. Although it has been shown that nuclear factor IA (Nfia) is a pivotal transcription factor for conferring gliogenic potential on neurogenic NS/PCs by sequestering DNA methyltransferase 1 (Dnmt1) from astrocyte‐specific genes, direct targets of Nfia that participate in astrocytic differentiation have yet to be completely identified. Here we show that SRY‐box transcription factor 8 (Sox8) is a direct target gene of Nfia at the initiation of the gliogenic phase. We found that expression of Sox8 augmented leukemia inhibitory factor (LIF)‐induced astrocytic differentiation, while Sox8 knockdown inhibited Nfia‐enhanced astrocytic differentiation of NS/PCs. In contrast to Nfia, Sox8 did not induce DNA demethylation of an astrocyte‐specific marker gene, glial fibrillary acidic protein (Gfap), but instead associated with LIF downstream transcription factor STAT3 through transcriptional coactivator p300, explaining how Sox8 expression further facilitated LIF‐induced Gfap expression. Taken together, these results suggest that Sox8 is a crucial Nfia downstream transcription factor for the astrocytic differentiation of NS/PCs in the developing brain.